PROVERBS IN SMS MESSAGES: ARCHAIC AND MODERN COMMUNICATION - Granbom-Herranen, Liisa (Proverbium - Yearbook, 2019)
Lectio praecursoria for public examination of the doctoral dissertation on 16 August 2018, Department of Folkloristics, University of Turku, Finland.